# Solve for y -7+4/7y=3 -7+47y=3
Combine 47 and y.
-7+4y7=3
Move all terms not containing y to the right side of the equation.
Add 7 to both sides of the equation.
4y7=3+7
Add 3 and 7.
4y7=10
4y7=10
Multiply both sides of the equation by 74.
74⋅4y7=74⋅10
Simplify both sides of the equation.
Simplify 74⋅4y7.
Cancel the common factor of 7.
Cancel the common factor.
74⋅4y7=74⋅10
Rewrite the expression.
14⋅(4y)=74⋅10
14⋅(4y)=74⋅10
Cancel the common factor of 4.
Factor 4 out of 4y.
14⋅(4(y))=74⋅10
Cancel the common factor.
14⋅(4y)=74⋅10
Rewrite the expression.
y=74⋅10
y=74⋅10
y=74⋅10
Simplify 74⋅10.
Cancel the common factor of 2.
Factor 2 out of 4.
y=72(2)⋅10
Factor 2 out of 10.
y=72⋅2⋅(2⋅5)
Cancel the common factor.
y=72⋅2⋅(2⋅5)
Rewrite the expression.
y=72⋅5
y=72⋅5
Combine 72 and 5.
y=7⋅52
Multiply 7 by 5.
y=352
y=352
y=352
The result can be shown in multiple forms.
Exact Form:
y=352
Decimal Form:
y=17.5
Mixed Number Form:
y=1712
Solve for y -7+4/7y=3

## Our Professionals ### Robert Kristofer ### Anna Frok ### Magnus Flores ### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top